2020
DOI: 10.1016/j.learninstruc.2020.101344
|View full text |Cite
|
Sign up to set email alerts
|

Learning by explaining orally or in written form? Text complexity matters

Abstract: AcknowledgementWe would like to thank Eleonora Dolderer, Maike Köncke, and Anna Rosenträger for their assistance in conducting the study and rating the qualitative data. Moreover, we would like to thank Christian Burkhart and Zarah Weiß for providing us with the computer-based text difficulty measures. The research reported in this article was supported by the Federal Ministry of Education and Research in Germany (BMBF) under contract number 01JA1611.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 68 publications
4
95
4
Order By: Relevance
“…Another consideration is whether students should generate written or oral explanations. Research suggests that while written explanations tend to be more organized, oral explanations are more elaborative and comprehensive, and result in deeper learning (Jacob et al, 2020; Lachner et al, 2018). Oral explanations also tend to involve more social presence, reflected by greater use of audience‐directed speech (e.g., first‐ and second‐person pronouns; Lachner et al, 2018; Hoogerheide et al, 2016).…”
Section: When Does Explaining To Others Support Learning?mentioning
confidence: 99%
See 1 more Smart Citation
“…Another consideration is whether students should generate written or oral explanations. Research suggests that while written explanations tend to be more organized, oral explanations are more elaborative and comprehensive, and result in deeper learning (Jacob et al, 2020; Lachner et al, 2018). Oral explanations also tend to involve more social presence, reflected by greater use of audience‐directed speech (e.g., first‐ and second‐person pronouns; Lachner et al, 2018; Hoogerheide et al, 2016).…”
Section: When Does Explaining To Others Support Learning?mentioning
confidence: 99%
“…Oral explanations also tend to involve more social presence, reflected by greater use of audience‐directed speech (e.g., first‐ and second‐person pronouns; Lachner et al, 2018; Hoogerheide et al, 2016). A recent study by Jacob et al (2020) found the benefits or oral explanations may depend on the complexity of the learning materials. Generating an oral explanation was more effective when learning from complex texts, and these benefits were mediated by greater comprehensiveness and social presence in students' explanations.…”
Section: When Does Explaining To Others Support Learning?mentioning
confidence: 99%
“…Recent research replicated the beneficial of explaining in non-interactive settings, in which no recipient was present; thus, students explained learned material to a fictitious peer which also resulted in higher learning outcomes [1,9,10]. Moreover, learning by explaining was more often shown to be effective when students were required to generate oral explanations instead of written ones [11][12][13]. A possible reason for the benefit of oral explaining might be the difference between perceived social presence during explaining.…”
Section: Introductionmentioning
confidence: 80%
“…Learning by explaining is commonly implemented in interactive learning settings in which students explain learned contents to present and interactive peers; this setting allows students to exchange ideas and thought, which additionally enhances their understanding [6,7,31,[37][38][39][40][41][42][43][44][45][46][47]. Interestingly, recent research started to investigate the effectiveness of explaining to a fictitious peer and reported promising results [1,2,4,12,13,23]. For instance, Fiorella and Mayer [1] conducted an experiment in which university students first studied a text with the expectation to either answer a test (test expectancy) or to explain the content to a fictitious peer (explaining expectancy) after a learning phase.…”
Section: Learning By Explaining To Fictitious Peersmentioning
confidence: 99%
“…The text was about immunology and dealt with immune research based on laboratory mice. The text was previously used in a study on learning by explaining [13]. Overall, the text had a length of 397 words and constituted a relatively complex text regarding common measures of text difficulty [13].…”
Section: Study Textmentioning
confidence: 99%